2014
DOI: 10.1111/ejn.12604
|View full text |Cite
|
Sign up to set email alerts
|

Region‐ and domain‐dependent action of nomifensine

Abstract: The dopamine (DA) terminal fields in the rat dorsal striatum (DS) and nucleus accumbens core (NAcc) are organized as patchworks of domains that exhibit distinct kinetics of DA release and clearance. The present study used fast-scan cyclic voltammetry recordings of electrically evoked DA overflow to test the hypothesis that nomifensine might exhibit domain-dependent actions within the NAcc, as we previously found to be the case within the DS. Within the NAcc, nomifensine preferentially enhanced evoked dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Our observation of DAT-dependent 5HT transport in regions of the basal ganglia is consistent with earlier studies documenting GBR-mediated reduction of 5HT uptake in striatum (Callaghan et al, 2005; Shu et al, 2014) as well as with evidence that striatal concentrations of 5HT and 5HT metabolites are increased by selective DAT inhibition in normal or SERT knock-out animals (Shen et al, 2004; Wong et al, 1995). In our molecular fMRI studies, GBR-mediated k U suppression was most pronounced in the CPu, an area known for high DAT expression (Ciliax et al, 1995; Richfield, 1991), where inhibition of 5HT removal was consistently observed in the presence of free 5HT concentrations that peaked from 0.6 to 6 μM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation of DAT-dependent 5HT transport in regions of the basal ganglia is consistent with earlier studies documenting GBR-mediated reduction of 5HT uptake in striatum (Callaghan et al, 2005; Shu et al, 2014) as well as with evidence that striatal concentrations of 5HT and 5HT metabolites are increased by selective DAT inhibition in normal or SERT knock-out animals (Shen et al, 2004; Wong et al, 1995). In our molecular fMRI studies, GBR-mediated k U suppression was most pronounced in the CPu, an area known for high DAT expression (Ciliax et al, 1995; Richfield, 1991), where inhibition of 5HT removal was consistently observed in the presence of free 5HT concentrations that peaked from 0.6 to 6 μM.…”
Section: Discussionsupporting
confidence: 92%
“…Efforts to characterize neurotransmitter reuptake and redistribution patterns could also facilitate better understanding of neuropharmacological therapies (Kirsch et al, 2008; Kirsch et al, 2002), and might inform the development of improved treatments. Real-time measurements of serotonin (5HT), dopamine, and norepinephrine clearance in laboratory animals have been performed using chronamperometry and voltammetry (Bucher and Wightman, 2015), revealing some regional differences in uptake parameters and susceptibility to pharmacological perturbations (Callaghan et al, 2005; Park et al, 2010; Shu et al, 2014). Because these measurements sample only discrete points in the brain however, they are ill suited to large-scale mapping of kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the dopamine “hotspots” identified in the in vivo FSCV literature (May and Wightman, 1989; Moquin and Michael, 2009; Shu et al, 2013; Taylor et al, 2015) may correspond to striosome or matrix compartments, depending on the striatal region. Additionally, the “hotspot” differences in cocaine sensitivity or DAT inhibition described in the literature may be attributable to striosome/matrix compartment differences described in the current study (Cass et al, 1992; Cline et al, 1995; Glynn and Yamamoto, 1989; Mitch Taylor et al, 2012; Shu et al, 2014). Alternatively, the differences observed in these dopamine “hotspots” may be attributable to a confluence of factors including differences in dopamine terminal or dopamine neuron sensitivity to drugs of abuse (Covey et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
“…The amplitude and duration of overshoot are sensitive to DAT inhibitors including nomifensine. [24][25][26]44 Past interpretations of overshoot as a sign of diffusion gaps 21,42 need to be reconsidered given our new data that speak against the presence of diffusion gaps ( Figure 6). …”
Section: Acs Chemical Neurosciencementioning
confidence: 93%
“…38 Figure 6 strongly supports the point of view that FSCV responses are not distorted by diffusion gaps but rather reflect the kinetic characteristics of DA terminals in close proximity to the recording electrode. 26,28 Kinetic Modeling: Two Parameter Sets Produce Identical Results. The restricted diffusion model reproduces some responses with two sets of adjustable parameters (see Supporting Information Table S1).…”
Section: Research Articlementioning
confidence: 99%